Protesting the Paradigm: A Comparative Study of News Coverage of Protests in Brazil, China, and India. (April 2016) - Shahin, Saif; Zheng, Pei; Sturm, Heloisa Aruth; Fadnis, Deepa
This study assesses the scope and applicability of the "protest paradigm" in non-Western contexts by examining the news coverage of Brazilian, Chinese, and Indian protests in their domestic media. Two publications from each nation, one conservative and one progressive, are content analyzed for adherence to a series of marginalization devices that have often been used by the U.S. media to ridicule protest movements and portray them as violent. The Indian media emerge as the least likely to follow the protest paradigm, while Brazilian and Chinese media conform to it in moderate levels. Comparative analysis suggests the historical legitimacy of informal power negotiations in a political culture makes news media more willing to take protesters seriously and limits adherence to the protest paradigm. In contrast, a news organization's ideological affiliation with the government of the day, rather than any ideology per se, makes it relatively more likely to conform to the protest paradigm. Marginalization devices such as circus, appearance, and eyewitness accounts are rarely used in any of these nations. But disparity of sources, (non)reference to protesters' causes and violence, and violence blame appear to be abiding features of news coverage of protests everywhere.